2002
DOI: 10.1902/jop.2002.73.8.877
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Reactivity for Porphyromonas gingivalis and Prevotella spp. in Supraand Subgingival Plaques, and Periodontal Clinical Parameters According to Subject Age

Abstract: The increase in probing depth with increasing age was not affected by the occurrence of periodontopathic bacteria. The high rate of occurrence of Pg, together with Pi and Pn, in subgingival plaque of the adult age groups was suggested to be associated with the high frequency of periodontal disease in the older age groups (above 30 to 49 years of age). The IBA appears to be useful for the efficient and rapid detection of periodontopathic bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…As epidemiological data support that incidence of periodontal disease increases with age [18,19], and our data using wild type Pg indicated that BMM from aged mice displayed an overall trend of reduced ability to produce immune mediators as compared to that of young mice. We speculated that one possibility for the increased incidence of periodontal disease in aged populations may reflect the reduced function of immune response and an attenuated strain of Pg can induce immune response similar to a virulent Pg strain.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…As epidemiological data support that incidence of periodontal disease increases with age [18,19], and our data using wild type Pg indicated that BMM from aged mice displayed an overall trend of reduced ability to produce immune mediators as compared to that of young mice. We speculated that one possibility for the increased incidence of periodontal disease in aged populations may reflect the reduced function of immune response and an attenuated strain of Pg can induce immune response similar to a virulent Pg strain.…”
Section: Resultssupporting
confidence: 72%
“…Periodontal disease is increasingly more common in adults as they age, suggesting that aging influences periodontal disease [18,19,50,51]. Despite this clear epidemiological connection, the mechanisms underlying aging and increased incidence/progression of periodontal disease are poorly understood; however, inflammatory response contributes significantly to periodontitis-associated tissue destruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few studies, however, that examine microbial colonization and gingival health during childhood in healthy populations 12 . Thus, the relationship between clinical parameters such as gingival index (GI) and the distribution of several periodontal pathogens in children is not yet well understood 13 .…”
Section: Introductionmentioning
confidence: 99%